Wireless sensor network for smart power metering. (24th August 2017) - Ševčík, Peter; Žák, Samuel; Hodoň, Michal
Summary: In this paper, the problematic of power metering is targeted. Places with shared power sources, where electricity usage is calculated equally according to the number of users, are often misused by single users for illegitimate power usage. Special wireless sensor network was developed and implemented in a scenario of multi‐store parking garage to solve this problem. This paper is an extended version of the paper published in the iNetSApp'15 section of the FedCSIS 2015 IEEE international conference. This paper is supplemented with measured waveforms of mains magnitudes for concrete electrical appliances (bulb, refrigerator, and electric motor). Copyright © 2017 John Wiley & Sons, Ltd.